Pooling of Urine Specimens for Diagnosis of Asymptomatic Chlamydia Trachomatis Infection by PCR in a Population of Low Frequency, a Cost-Saving Technique for Epidemiological and Screening Programs - Chaudhary, Nawwal Naeem; Mirza, Irfan Ali; Khurshid, Umar; Muhammad, Ammarah Iqbal; Gullalai, Shazia; Naqvi, Sakeenah Hussain (Pakistan Armed Forces Medical Journal, 2024)
Objective: To describe the frequency of Chlamydia trachomatis in local community visiting a tertiary care hospital and to estimate the cost saving achieved as a result of pooling strategy. Study Design: Cross-sectional study. Place and Duration of Study: Department of Microbiology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Jan 2022 to Jun 2022. Methodology: A pool of three urine samples was created after individual manual DNA extraction of each sample and tested by RT PCR. Any pool signaling positive was identified and all samples in that pool were retested individually to determine the positive sample. A total of 66 asymptomatic young people including males and females were tested. Results: The frequency of Chlamydia trachomatis was found to be 7.57%. About 22 pools were created resulting in a 48.0% savings in costs. Conclusion: The Pooling strategy adopted with the objective of saving test costs resulted in getting timely and reliable results in a resource limited setting. It also provided with the means to keep Sexually Transmitted Infections detection programs going on at various healthcare levels and in screening a larger number of populations.